A case of giant lipoma of parietal peritoneum with literature review - B, Bharath; Reddy, G. Sagar; Francis, John (Journal of Surgery and Medicine, 2022)
Lipomas are the most typically diagnosed soft tissue tumors. A lipoma is composed of adipose tissue, may vary in size, and is usually seen in the subcutaneous region, most commonly over the extremities followed by trunk and neck. In this case report, a rare case of giant lipoma that was found in the preperitoneal space arising from the parietal peritoneum measuring 40 x 36 x 5 cm and weighing 3.7 kg is described. This lipoma was successfully excised without any immediate or late post-operative complications and no recurrence for 24 months post-operatively.